Urbanization and Structural Transformation - Michaels, G.; Rauch, F.; Redding, S. J. (Quarterly Journal of Economics, 2012)
We examine urbanization using new data that allow us to track the evolution of population in rural and urban areas in the United States from 1880 to 2000. We find a positive correlation between initial population density and subsequent population growth for intermediate densities, which increases the dispersion of the population density distribution over time. We use theory and empirical evidence to show this pattern of population growth is the result of differences in agriculture's initial share of employment across population densities, combined with structural transformation that shifts employment away from agriculture. Copyright 2012, Oxford University Press.